THE RELATIONSHIP BETWEEN RESILIENCE AND PSYCHOLOGIZCAL COMPLAINTS AMONG MENOPAUSE WOMEN IN DUSUN 1 TAMBAH REJO - Puput Tri Widiyanti; Surmiasih Surmiasih; Rini Palupi; Anggi Kusuma (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2026)
Background: Menopause is the stage when women experience their last natural menstruation, which occurs between the ages of 45 and 55 years. Menopausal women experience various physical and psychological complaints during menopause, Based on data on psychological symptoms in menopausal women found that the symptoms felt were difficulty sleeping 37%, quickly tired at work 35%, often forgetful 33%, easy to endure 26%. In the psychological context, resilience is an important factor in dealing with psychological complaints because it helps individuals to adapt to stress, overcome problems, and maintain health. This study aims to determine the relationship between resilience and psychological complaints in menopausal women in Dusun 1 Tambah Rejo. Method: : This study was a quantitative correlational study with a cross-sectional approach. The population was all 46 menopausal women in Hamlet 1 Tambah Rejo. The sampling technique used was total sampling. The instruments used were the Connor-Davidson Resilience Scale (CD-RISC) and the Menopause Rating Scale (MRS) questionnaires. Data analysis was performed using the gamma test. Results: The results showed that the majority of respondents had a high level of resilience (50,0%) and moderate psychological complaints (30,4%). The statistical test results obtained a p-value of 0.001 (<0.05), indicating a significant relationship between resilience and psychological complaints in menopausal women in Hamlet 1 Tambah Rejo. It is hoped that menopausal women will improve their resilience through positive activities to reduce psychological complaints that arise during menopause. Conclusion: There is a relationship between resilience and psychological complaints in menopausal women in Dusun 1 Tambah rejo Keywords: Resilience, Psychological Complaints, Menopause